(untitled) (International journal of artificial intelligence, 2025)
This thesis explores modern approaches in the theory and methodology of teaching and education at the primary level. Special attention is given to learner-centered instruction, integration of digital tools, and the role of moral and social upbringing in early childhood education. The paper highlights effective strategies to improve learning outcomes and foster holistic development of young learners.